Materiais nanoestruturados para eletrodo e eletrólito de supercapacitores - Raquel Silveira Borges (2013)
Electrochemical capacitors based on carbon nanostructured materials and ionic liquids were studied by impedance spectroscopy, cyclic voltammetry and galvanostatic charge/discharge cycles. Previously to the capacitor studies ionic liquids with different cations were characterized in order to select the best type of ionic liquid to use as electrolyte in energy storage devices. The ionic liquid 1-Butyl-2,3-dimethylimidazolium bis(trifluoromethylsulfonyl)imide was chosen due to its high ionic conductivity, mS.cm-1 at room temperature, and its elevate electrochemical stability. This ionic liquid was used to prepare a new type of composite electrolyte based on the ionic liquid and montmorillonite clay. The composite electrolyte presented a slightly reduction in ionic conductivity values compared to neat ionic liquid. However, this conductivity reduction was compensated to improvement of work temperature and mechanical stability of this composite electrolyte. Different kinds of carbon materials were used to prepare electrodes: functionalized double-walled carbon nanotubes, graphene oxide nanosheets and reduced graphene oxide nanosheets. Electrodes were analyzed by scanning electron microscopy showing morphological differences for each kind of nanomaterial used. Electrochemical capacitors using the best ionic liquid were studied with the ionic liquid supported in a filter paper and with the new composite electrolyte (ionic liquid:clay). Solid electrochemical capacitor results were promising. Specific capacitance of 104 F/g was reached at 200°C and 4V potential. Furthermore the capacitor behavior of the devices working at 200°C was established. The maximum temperature work to electrochemical capacitors previously reported was 100°C. Energy density of 17 Wh/Kg was reached at 120°C and 200°C, those values are in the same range of results reported in literature.